(untitled) (Journal of Bio-Science, 2026)
Petroleum ether (PE), chloroform (CHCl3), and methanol (CH3OH) extracts of the whole Cassia tora Linn. plant were evaluated by dose-mortality tests and for their repellent activity against Callosobruchus chinensis L., Sitophilus oryzae L., and Tribolium castaneum (Hbst.), their cytotoxicity against Artemia salina L. nauplii, their larvicidal activity against Culex quinquefasciatus Say larvae, and their piscicidal activity against the fish Poecilia reticulata Peters, under laboratory conditions. In the dose-mortality test, the PE and CH3OH extracts of the tested plant showed favorable results against C. chinensis, the PE extract was the most active with an LD50 of 1.51 mg/cm² after 48 h of exposure. Against S. oryzae, the PE extract showed the highest activity with an LD50 of 0.62 mg/cm² after 48 h of exposure. And against T. castaneum, only the PE and CH3OH extracts of the tested plant caused mortality, while the PE extract was more active with an LD50 of 0.82 mg/cm² after 48 h of exposure. However, the C. tora extract with CHCl3 induced no mortality in C. chinensis or T. castaneum. In the repellent test, with the exception of the PE and CHCl3 extracts against T. castaneum, all extracts showed significant repellent activity against C. chinensis, S. oryzae, and T. castaneum. Regarding the cytotoxicity test, all C. tora extracts reacted against A. salina nauplii, with the PE extract proving the most effective, with a minimum LC50 of 33.54 ppm after 48 h of exposure. Against C. quinquefasciatus larvae, the CHCl3 extract exhibited the highest larvicidal activity, with an LC50 of 60.93 ppm after 48 h of exposure. During the piscicidal activity test, only the CH3OH extracts of the tested plant showed promising results against the fish P. reticulata, with an LC50 of 28.85 ppm after 48 h of exposure. In contrast, the PE and CHCl3 extracts of C. tora were not lethal to P. reticulata. J. Bio-Sci. 33(1): 101-112, 2025